P2M-WBF: PELATIHAN PENINGKATAN KONDISI FISIK ATLET PELATNAS TAEKWONDO INDONESIA DI POPKI CIBUBUR - Fahmy Fachrezzy; Uzizatun Maslikah; Masnur Ali; Viranti Citrasari (Indonesian Collaboration Journal of Community Services, 2023)
P2M-WBF is a community service program for the fostered area of ??the Faculty of Jakarta State University with the Indonesian Taekwondo National Training Center at POPKI Cibubur Jl. Karya Bakti, RT.8/RW.7, Cibubur, Kec. Ciracas, City of East Jakarta, Special Capital Region of Jakarta 13720. The aim of this Community Service Program is to carry out training and assistance to improve the physical condition of Indonesian National Taekwondo National Training Athletes in preparation for the Championships. The method of carrying out the activity is the instructor method which comes from licensed trainers who have qualifications in the field of Nationally licensed Physical Conditions Training. While the material to be provided in the implementation of community service consists of: Providing subject matter which includes: 1) forms and models of physical exercise; 2) Carry out theoretical and practical evaluations. The objectives of this activity are: 1) As an effort to increase knowledge, understanding and skills for Indonesian Taekwondo Athletes regarding physical condition training programs; 2) as an effort to improve the quality and human resources, especially the Indonesian Taekwondo National Training Athletes